High-strength steel plate with excellent hole expandability and its manufacturing method

A high-strength steel plate with a tailored alloy composition and annealing process addresses moldability and hole expandability issues, ensuring high strength, low yield ratio, and improved ductility for automobile structural members.

JP7600377B2Active Publication Date: 2024-12-16POHANG IRON & STEEL CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023514003
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-07
Filing Date
2021-09-07
Publication Date
2024-12-16
Estimated Expiration
2041-09-07

AI Technical Summary

Technical Problem

High-strength steels used in automobile structural members face challenges with low elongation rates, poor moldability, and low hole expandability, leading to defects such as cracks during press molding and reduced safety in collisions.

Method used

A high-strength steel plate with a specific alloy composition (C: 0.05 to 0.15%, Si: 0.5% or less, Mn: 2.0 to 3.0%, Ti: 0.1% or less, Nb: 0.1% or less, Cr: 1.5% or less, P: 0.1% or less, S: 0.01% or less, balanced with Fe and unavoidable impurities) and a controlled microstructure of 35-60% ferrite, 40-50% bainite, and trace martensite and retained austenite, combined with a unique continuous annealing process to refine hard phases and control crystal grain shape.

Benefits of technology

The steel plate achieves high strength with excellent hole expandability and formability, preventing processing defects and enhancing crash resistance by ensuring a low yield ratio and high ductility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600377000004
    Figure 0007600377000004
  • Figure 0007600377000005
    Figure 0007600377000005
  • Figure 0007600377000006
    Figure 0007600377000006
Patent Text Reader

Abstract

The present invention provides a high-strength steel sheet that is a suitable material for use in automotive structural components, etc., and that has a low yield ratio and high strength while having excellent formability such as hole expandability due to improved ductility, and a method for producing the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel suitable as a material for automobiles, and more particularly to a high-strength steel sheet having excellent hole expandability and a method for producing the same. [Background technology]

[0002] Recently, in the field of the automobile industry, various environmental regulations and energy usage regulations have led to a demand for the use of high strength steel in order to improve fuel efficiency or durability.

[0003] In particular, as regulations regarding the impact stability of automobiles have expanded, high-strength steel, which has excellent strength, has been adopted as a material for structural members such as members, seat rails, pillars, etc. to improve the impact resistance of the vehicle body.

[0004] These automobile parts have complex shapes according to the design and stability, and are mainly manufactured by forming using a press die, so they require a high level of formability as well as high strength.

[0005] While the higher the strength of steel, the better it is at absorbing impact energy, there is a problem that, generally, as the strength increases, the elongation decreases, which reduces formability. Furthermore, if the yield strength is excessively high, the flow of the material into the die during forming is reduced, resulting in poor formability.

[0006] In addition, since automotive parts have many forming areas that expand after holes are drilled, hole expandability is required for smooth forming, but high-strength steel has a problem that it has low hole expandability and defects such as cracks occur during forming. Thus, if the hole expandability is poor, cracks may occur in the hole forming areas during a car collision, easily destroying the parts and threatening the safety of passengers.

[0007] On the other hand, representative high-strength steels used as automotive materials include dual phase steel (DP steel), transformation induced plasticity steel (TRIP steel), complex phase steel (CP steel), ferrite bainite steel (FB steel), etc.

[0008] DP steel, which is an ultra-high tensile steel, has a low yield ratio of about 0.5 to 0.6, making it easy to process, and has the advantage of having the second highest elongation rate after TRIP steel. For this reason, it is mainly used in door outers, seat rails, seat belts, suspensions, arms, wheel discs, etc.

[0009] TRIP steel has a yield ratio in the range of 0.57 to 0.67, and is therefore characterized by excellent formability (high ductility), making it suitable for parts that require high formability, such as members, loops, seat belts, bumper rails, etc.

[0010] CP steel has a low yield ratio, high elongation and bending workability, and is therefore used for side panels, underbody reinforcements, etc. FB steel has excellent hole expansibility, and is mainly used for suspension lower arms, wheel discs, etc.

[0011] Among these, DP steel is mainly composed of ferrite with excellent ductility and hard phases (martensite phase, bainite phase) with high strength, and may contain a small amount of retained austenite. Such DP steel has low yield strength and high tensile strength, so it has low yield ratio (YR), high work hardening rate, high ductility, continuous yield behavior, room temperature aging resistance, bake hardenability, etc. In addition, when the fraction and shape of the bainite phase in the structure are controlled, it can be manufactured as a high-strength steel with high hole expandability.

[0012] However, in order to secure ultra-high strength of tensile strength of 980 MPa or more, the fraction of hard phases such as martensite, which is advantageous for improving strength, must be increased. In this case, the yield strength increases, which can cause defects such as cracks during press forming.

[0013] Generally, DP steel for automobiles is manufactured by producing slabs through the steelmaking and continuous casting processes, and then the slabs are heated, roughly rolled, and finished hot rolled to obtain hot-rolled coils, which are then annealed to produce the final product.

[0014] Here, the annealing process is a process that is mainly performed during the manufacture of cold-rolled steel sheets. The cold-rolled steel sheets are manufactured by pickling a hot-rolled coil to remove surface scale, cold-rolling the hot-rolled coil at a certain rolling reduction at room temperature, and then passing through an annealing process and an additional temper rolling process as necessary.

[0015] The cold-rolled steel sheet (cold-rolled material) obtained by cold rolling is itself in a very hard state and is not suitable for manufacturing parts that require workability. Therefore, in a subsequent process, the cold-rolled steel sheet is softened by heat treatment in a continuous annealing furnace to improve its workability.

[0016] As an example, the annealing process involves heating a steel sheet (cold-rolled material) to about 650 to 850°C in a heating furnace and then maintaining it for a certain period of time, which reduces the hardness and improves workability through recrystallization and phase transformation phenomena.

[0017] A steel sheet that has not been annealed has high hardness, particularly surface hardness, and is insufficient in workability, whereas a steel sheet that has been annealed has a recrystallized structure, which reduces hardness, yield point, and tensile strength, thereby improving workability.

[0018] A representative method for reducing the yield strength of DP steel is to completely recrystallize ferrite in the heating process during continuous annealing to produce an equiaxed crystal form, and then, in the subsequent process, when austenite is generated and grows, the equiaxed crystal form is formed, thereby forming a uniform austenite phase with a small grain size.

[0019] As shown in Figure 1, the continuous annealing process is carried out through the following zones in an annealing furnace: heating zone, soaking zone, slow cooling zone, quenching zone, and overaging zone. During this process, a fine ferrite phase is formed by sufficient recrystallization in the heating zone, and then a small and uniform austenite phase is formed from the fine ferrite phase in the soaking zone. After that, the ferrite phase is recrystallized while forming fine bainite and martensite phases from the austenite during cooling.

[0020] On the other hand, as a conventional technique for improving the workability of high-strength steel, Patent Document 1 presents a method of refining the structure, specifically, a method of dispersing fine precipitated copper particles with a particle size of 1 to 100 nm inside the structure of a dual-phase steel sheet mainly composed of martensite phase. However, this technique requires the addition of 2 to 5% Cu to obtain good fine precipitated phase particles, and therefore there is a risk of red brittleness due to the large amount of Cu, and there is a problem that the manufacturing cost increases excessively.

[0021] Patent Document 2 discloses a high-strength steel sheet having a structure containing 2-10% by area of ​​pearlite in a ferrite matrix, and resulting from precipitation strengthening and grain refinement by adding carbonitride-forming elements (ex, Ti, etc.). This technology has the advantage of being able to easily achieve high strength compared to low manufacturing costs, but it is found that heating to a fairly high temperature during continuous annealing is required to ensure high ductility through sufficient recrystallization, since the recrystallization temperature rises sharply due to fine precipitation. In addition, conventional precipitation-strengthened steel, which is strengthened by precipitating carbonitrides in a ferrite matrix, has a limit in obtaining high strength of 600 MPa or more.

[0022] Patent Document 3 discloses a technique for ensuring a martensite volume fraction of 80 to 97% by continuous annealing of steel material containing 0.18% or more carbon, water cooling to room temperature, and then overaging for 1 to 15 minutes at a temperature of 120 to 300° C. Although such a technique is advantageous for improving yield strength, it has problems such as poor coil shape quality due to temperature variations in the width and length directions of the steel plate during water cooling, and poor material quality depending on the location and reduced workability during processing such as roll forming.

[0023] In light of the above-mentioned prior art, in order to improve formability such as hole expandability of high strength steel, it is necessary to develop a method that can improve ductility while lowering yield strength. [Prior art documents] [Patent documents]

[0024] [Patent Document 1] Japanese Patent Publication No. 2005-264176 [Patent Document 2] Korean Patent Publication No. 2015-0073844 [Patent Document 3] Japanese Patent Publication No. 1992-289120 Summary of the Invention [Problem to be solved by the invention]

[0025] One aspect of the present invention is to provide a high-strength steel plate which is a suitable material for automotive structural members and has a low yield ratio and high strength while having excellent formability such as hole expandability due to improved ductility, and a method for producing the same.

[0026] The object of the present invention is not limited to the above. The object of the present invention can be understood from the entire contents of this specification, and a person having ordinary skill in the art to which the present invention pertains will have no difficulty in understanding the additional object of the present invention. [Means for solving the problem]

[0027] One aspect of the present invention provides a high-strength steel sheet having excellent hole expandability, which contains, by weight, 0.05 to 0.15% carbon (C), 0.5% or less silicon (Si), 2.0 to 3.0% manganese (Mn), 0.1% or less (excluding 0%) titanium (Ti), 0.1% or less (excluding 0%) niobium (Nb), 1.5% or less (excluding 0%) chromium (Cr), 0.1% or less phosphorus (P), 0.01% or less sulfur (S), the balance being Fe and unavoidable impurities, and has a microstructure composed of 35 to 60% ferrite in area fraction, 40 to 50% bainite, the balance being martensite and retained austenite, and the bainite phase has an average aspect ratio (major axis:minor axis) of 1.5 to 2.3:1.

[0028] Another aspect of the present invention includes a step of heating a steel slab having the above-mentioned alloy composition, a step of finish hot rolling the heated slab to an outlet temperature Ar3 to 1000 ° C. to produce a hot-rolled steel sheet, a step of coiling the hot-rolled steel sheet in a temperature range of 400 to 700 ° C., a step of cooling to room temperature after the coiling, and a step of cold rolling at a rolling reduction of 40 to 70% to produce a cold-rolled steel sheet after the cooling, a step of continuous annealing the cold-rolled steel sheet, a step of primary cooling to a temperature range of 650 to 700 ° C. after the continuous annealing, and a step of secondary cooling to a temperature range of 300 to 580 ° C. after the primary cooling, and the continuous annealing step is performed in a facility equipped with a heating zone, a soaking zone, and a cooling zone, and the end temperature of the heating zone is 10 ° C. or more higher than the end temperature of the soaking zone. A method for producing a high-strength steel sheet having excellent hole expandability is provided. Effect of the Invention

[0029] According to the present invention, it is possible to provide a steel sheet having excellent hole expandability and improved formability despite having high strength.

[0030] The steel sheet of the present invention, which has improved formability, can prevent processing defects such as cracks or wrinkles during press forming, and is therefore suitable for use in structural parts that require processing into complex shapes. Furthermore, the steel sheet of the present invention is also effective in producing materials with improved crash resistance so that defects such as cracks are not easily formed when an automobile using such parts inevitably crashes. [Brief description of the drawings]

[0031] [Figure 1] Schematic diagram of a heat treatment for a conventional continuous annealing process (CAL). [Diagram 2] 1 is a schematic diagram of a heat treatment diagram for a continuous annealing process (CAL) according to one embodiment of the present invention, shown together with the diagram in FIG. 1 (grey line). [Diagram 3] 1 shows a photograph of the microstructure of an example of the present invention according to one embodiment of the present invention. [Figure 4] 1 shows a photograph of a microstructure of a comparative example in accordance with an embodiment of the present invention. [Diagram 5] FIG. 2 is a schematic diagram showing the aspect ratio of bainite grains in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The inventors of the present invention have conducted extensive research in order to develop a material having a level of formability suitable for use in automotive components that require processing into complex shapes.

[0033] In particular, the inventors have confirmed that the target can be achieved by inducing sufficient recrystallization of the soft phase, which affects the ductility of the steel, and by refining the hard phase and controlling the crystal grain shape, which are advantageous for ensuring strength, and have thus completed the present invention.

[0034] The present invention will be described in detail below.

[0035] A high-strength steel plate with excellent hole expandability according to one embodiment of the present invention can contain, by weight, carbon (C): 0.05 to 0.15%, silicon (Si): 0.5% or less, manganese (Mn): 2.0 to 3.0%, titanium (Ti): 0.1% or less (excluding 0%), niobium (Nb): 0.1% or less (excluding 0%), chromium (Cr): 1.5% or less (excluding 0%), phosphorus (P): 0.1% or less, and sulfur (S): 0.01% or less.

[0036] The reasons for restricting the alloy composition of the steel plate provided in the present invention as described above will be described in detail below.

[0037] Meanwhile, in the present invention, unless otherwise specified, the content of each element is based on weight, and the proportion of the structure is based on area.

[0038] (Carbon (C): 0.05~0.15%) Carbon (C) is an important element that is added for solid solution strengthening. Such C combines with precipitated elements to form fine precipitates, thereby contributing to improving the strength of steel.

[0039] If the C content exceeds 0.15%, the hardening ability increases, and martensite is formed during cooling during the production of steel, resulting in an excessive increase in strength, but a decrease in elongation. In addition, the weldability is poor, and there is a risk of welding defects occurring when processing into parts. On the other hand, if the C content is less than 0.05%, it becomes difficult to ensure the target level of strength.

[0040] Therefore, the C content may be 0.05 to 0.15%. More advantageously, the C content may be 0.06% or more, and may be 0.13% or less.

[0041] (Silicon (Si): 0.5% or less) Silicon (Si) is a ferrite stabilizing element, which is advantageous in promoting ferrite transformation and ensuring the target level of ferrite fraction. It also has good solid solution strengthening ability and is effective in increasing the strength of ferrite, making it a useful element in ensuring strength without reducing the ductility of steel.

[0042] If the Si content exceeds 0.5%, the solid solution strengthening effect becomes excessive, which reduces ductility and induces surface scale defects, adversely affecting the surface quality of the plating. In addition, there is a problem that the chemical conversion treatability is impaired.

[0043] Therefore, the Si content may be 0.5% or less, 0% may be excluded, and more preferably 0.1% or more.

[0044] (Manganese (Mn): 2.0-3.0%) Manganese (Mn) is an element that is advantageous for solution strengthening of steel, as it causes sulfur (S) in steel to precipitate as MnS, preventing hot embrittlement due to the formation of FeS.

[0045] If the Mn content is less than 2.0%, not only are the above-mentioned effects not obtained, but it is also difficult to ensure the target level of strength. On the other hand, if the Mn content exceeds 3.0%, there is a high possibility that problems such as weldability and hot rolling will occur, and martensite will be formed more easily due to the increased hardenability, which may result in a decrease in ductility. In addition, there is a problem that Mn-Bands (bands of Mn oxides) are excessively formed in the structure, increasing the risk of defects such as processing cracks. And there is a problem that Mn oxides dissolve onto the surface during annealing, greatly impairing platability.

[0046] Therefore, the Mn content can be 2.0 to 3.0%, and more advantageously 2.2 to 2.8%.

[0047] (Titanium (Ti): 0.1% or less (excluding 0%)) Titanium (Ti) is an element that forms fine carbides and contributes to ensuring yield strength and tensile strength. In addition, Ti precipitates N in steel as TiN and inhibits the formation of AlN from Al, which is inevitably present in steel, and therefore reduces the possibility of cracks occurring during continuous casting.

[0048] If the Ti content exceeds 0.1%, coarse carbides are precipitated, and the strength and elongation may decrease due to the reduction in the carbon content in the steel. In addition, there is a risk of nozzle clogging during continuous casting, which increases the production cost.

[0049] Therefore, the Ti content may be 0.1% or less, and 0% may be excluded.

[0050] (Niobium (Nb): 0.1% or less (excluding 0%)) Niobium (Nb) is an element that segregates at the austenite grain boundaries, suppresses the coarsening of austenite crystal grains during annealing heat treatment, and forms fine carbides, thereby contributing to improving strength.

[0051] If the Nb content exceeds 0.1%, coarse carbides are precipitated, and the strength and elongation may decrease due to the reduction in the carbon content in the steel, resulting in problems such as increased manufacturing costs. Therefore, the Nb content may be 0.1% or less, and 0% may be excluded.

[0052] (Chromium (Cr): 1.5% or less (excluding 0%)) Chromium (Cr) is an element that facilitates the formation of the bainite phase and suppresses the formation of the martensite phase during annealing heat treatment, while forming fine carbides, thereby contributing to improving strength.

[0053] If the Cr content exceeds 1.5%, the bainite phase is excessively formed, which reduces the elongation, and if carbides are formed at the grain boundaries, the strength and elongation may decrease. In addition, there is a problem that the manufacturing cost increases.

[0054] Therefore, the Cr content may be 1.5% or less, and 0% may be excluded.

[0055] (Phosphorus (P): 0.1% or less) Phosphorus (P) is a substitutional element that has the greatest effect on solid solution strengthening, and is an element that is advantageous in improving in-plane anisotropy and ensuring strength without significantly reducing formability. However, if P is added in excess, there are problems in that the possibility of brittle fracture increases significantly, the possibility of slab breakage during hot rolling increases, and the surface properties of the coating are impaired.

[0056] Therefore, in the present invention, the P content can be controlled to 0.1% or less, and 0% can be excluded in consideration of the unavoidable added level.

[0057] (Sulfur (S): 0.01% or less) Sulfur (S) is an impurity element in steel that is inevitably added, and since it impairs ductility, it is preferable to control the S content as low as possible. In particular, since S has the problem of increasing the possibility of generating red shortness, it is preferable to control the S content to 0.01% or less, although 0% can be excluded in consideration of the level of S that is inevitably added during the manufacturing process.

[0058] The remaining component of the present invention is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and it is not possible to exclude them. Since such impurities are known to anyone skilled in the normal manufacturing process, the entire contents of the impurities will not be mentioned in this specification.

[0059] The steel sheet of the present invention having the above-mentioned alloy composition can have a microstructure composed of ferrite and hard phases, bainite phase and martensite phase.

[0060] Specifically, the steel sheet of the present invention may contain ferrite phase at an area fraction of 35 to 60%, bainite phase at 40 to 50%, and the remainder may contain martensite phase and a small amount of retained austenite phase.

[0061] If the bainite phase fraction is too high, the soft phase fraction will be relatively low and the target level of formability will not be ensured, whereas if the soft phase fraction is less than 40%, the hole expandability may decrease.

[0062] On the other hand, it is clear that it is advantageous for the fraction of the above-mentioned retained austenite phase not to exceed 3%, and that even if it is 0%, it is not difficult to ensure the intended physical properties.

[0063] In the steel sheet of the present invention, when the bainite phase is contained in the above-mentioned fraction range, the shape of the bainite phase is controlled, whereby the target formability can be more advantageously ensured.

[0064] Specifically, the bainite phase preferably has an average aspect ratio (major axis:minor axis) of 1.5 to 2.3:1.

[0065] If the average aspect ratio of bainite exceeds 2.3, deformation and stress are locally concentrated in the bainite distributed in the rolling direction, resulting in a problem of reduced ductility. There is no particular need to set a lower limit for the average aspect ratio of the bainite phase, but taking into consideration the shape of the bainite phase due to processing, the lower limit of the average aspect ratio can be set to 1.5 or more.

[0066] In the present invention, the aspect ratio means the ratio of the length (long diameter) to the width (short diameter) of the grain size in the rolling direction (long diameter:short diameter), as shown in Fig. 5, for example. In Fig. 5, (a) is a schematic diagram showing a bainite grain size having an aspect ratio of about 1:1, and (b) is a schematic diagram showing a bainite grain size having an aspect ratio at a level limited by the present invention. In the present invention, the aspect ratio value means the average aspect ratio value of the bainite grains.

[0067] On the other hand, among the phases constituting the hard phase, the martensite phase is not specifically limited in its fraction, but in order to ensure ultra-high strength of tensile strength of 980 MPa or more, the martensite phase can be contained in a maximum of 15 area % of the total structure fraction, and preferably 15 area % or less (excluding 0%).

[0068] The steel sheet of the present invention having the above-mentioned microstructure has a tensile strength of 980 MPa or more, a yield strength of 680 MPa or less, an elongation (total elongation) of 13% or more, and a yield ratio of 0.7 or less, and can have the properties of high strength, high ductility, and a low yield ratio.

[0069] Furthermore, the above steel sheet has a hole expansion ratio (HER) of 30% or more, and thus can have an excellent hole expandability effect.

[0070] Hereinafter, a method for producing a high-strength steel plate having excellent hole expandability according to another aspect of the present invention will be described in detail.

[0071] In short, the present invention can produce the desired steel sheet through the steps of "steel slab heating - hot rolling - coiling - cold rolling - continuous annealing." Each step will be described in detail below.

[0072] [Steel slab heating] First, a steel slab satisfying the above-mentioned alloy composition can be prepared and then heated.

[0073] This process is carried out in order to smoothly carry out the subsequent hot rolling process and to sufficiently obtain the target physical properties of the steel sheet. In the present invention, the conditions of such a heating process are not particularly limited, and normal conditions may be used. As an example, the heating process can be carried out in a temperature range of 1100 to 1300°C.

[0074] [Hot rolling] The steel slab heated as described above can be hot rolled to produce a hot rolled steel sheet, and at this time, finish hot rolling can be performed at an outlet temperature of Ar3 or more and 1000°C or less.

[0075] If the temperature at the outlet side during the above-mentioned finish hot rolling is less than Ar3, the hot deformation resistance increases rapidly, the top, tail and edges of the hot rolled coil become single-phase regions, and the in-plane anisotropy increases, which may result in a decrease in formability. On the other hand, if the temperature exceeds 1000°C, the rolling load decreases relatively, which is advantageous for productivity, but there is a risk of a thick oxide scale being generated.

[0076] More specifically, the finish hot rolling can be carried out in the temperature range of 760 to 940°C.

[0077] [Winding] The hot-rolled steel sheet produced as described above can be wound into a coil.

[0078] The coiling can be performed at a temperature range of 400 to 700° C. If the coiling temperature is lower than 400° C., the excessive formation of martensite or bainite may cause an excessive increase in strength of the hot-rolled steel sheet, which may cause problems such as defective shape due to load during subsequent cold rolling. On the other hand, if the coiling temperature exceeds 700° C., there is a problem that the surface scale increases and pickling properties are reduced.

[0079] [cooling] The coiled hot-rolled steel sheet is preferably cooled to room temperature at an average cooling rate of 0.1° C. / s or less (excluding 0° C. / s). In this case, the coiled hot-rolled steel sheet may be cooled after being transported, stacked, etc., but the process before cooling is not limited thereto.

[0080] In this manner, by cooling the coiled hot-rolled steel sheet at a constant speed, it is possible to obtain a hot-rolled steel sheet in which carbides that serve as nucleation sites for austenite are finely dispersed.

[0081] [Cold rolling] The hot-rolled steel sheet coiled as described above can be cold-rolled to produce a cold-rolled steel sheet.

[0082] At this time, the cold rolling can be carried out at a cold rolling reduction rate of 40 to 70%. If the cold reduction is less than 40%, the driving force for recrystallization is weakened, making it difficult to obtain good recrystallized grains, whereas if the cold reduction is more than 70%, there is a high possibility that cracks will occur at the edges of the steel sheet, and the rolling load may increase rapidly.

[0083] The present invention reveals that the hot-rolled steel sheet can be pickled before the cold rolling, and the pickling process can be carried out in a conventional manner.

[0084] [Continuous annealing] It is preferable to subject the cold rolled steel sheet produced as described above to a continuous annealing process. As an example, the continuous annealing process can be performed in a continuous annealing furnace (CAL).

[0085] Typically, a continuous annealing furnace (CAL) can be composed of a heating zone, a soaking zone, a cooling zone (slow cooling zone and quenching zone), and an overaging zone. A cold-rolled steel sheet is charged into such a continuous annealing furnace, heated to a specific temperature in the heating zone, and after the target temperature is reached, the steel sheet is maintained for a certain period of time in the soaking zone.

[0086] In the present invention, we have attempted to develop a method for applying sufficient heat input to a steel sheet in a heating zone consisting of a heating zone and a soaking zone during continuous annealing in order to obtain fine bainite and martensite phases together with recrystallized ferrite as the final fine structure.

[0087] Specifically, in a typical continuous annealing process, the final temperature of the heating zone and the temperature of the soaking zone are controlled in the same manner, whereas the present invention is characterized in that the temperatures of the heating zone and the soaking zone are controlled independently.

[0088] In other words, in a typical continuous annealing process, the start temperature and end temperature of the soaking zone are controlled in the same way, which means that the end temperature of the heating zone and the start temperature of the soaking zone are the same.

[0089] In contrast, in the present invention, the temperature of the heating zone is controlled to be higher than the temperature of the soaking zone, thereby further promoting the recrystallization of ferrite in the heating section, thereby inducing the formation of fine ferrite and allowing the austenite formed at the ferrite grain boundaries to be small and uniform.

[0090] Preferably, in the present invention, the end temperature of the heating zone is controlled to be 10° C. or more higher than the end temperature of the soaking zone, and more preferably, the following relational expression can be satisfied.

[0091] [Equation] 10≦End temperature of heating zone-end temperature of soaking zone (℃)≦40

[0092] That is, in the present invention, when the end temperature of the heating zone is controlled to be higher than the end temperature of the soaking zone, and the temperature difference is less than 10° C., ferrite recrystallization is delayed, making it difficult to obtain a fine and uniform austenite phase. On the other hand, when the temperature difference exceeds 40° C., the subsequent cooling step is not performed sufficiently due to the excessive temperature difference, and there is a risk that coarse bainite or coarse martensite phase is formed in the final structure.

[0093] In the present invention, the end temperature of the heating zone may be 790 to 830°C, but if the temperature is less than 790°C, sufficient heat input for recrystallization cannot be applied, while if the temperature exceeds 830°C, the productivity decreases, the austenite phase is excessively formed, the fraction of the hard phase after subsequent cooling increases significantly, and the ductility of the steel may decrease.

[0094] The end temperature of the soaking zone may be 760 to 790° C. If the temperature is less than 760° C., excessive cooling is required at the end temperature of the heating zone, which is economically disadvantageous and the amount of heat required for recrystallization may be insufficient. On the other hand, if the temperature exceeds 790° C., the austenite fraction becomes excessive and exceeds the fraction of the hard phase during cooling, which may reduce formability.

[0095] In addition, in the present invention, the temperature difference between the end temperature of the heating zone and the end temperature of the soaking zone can be realized by cutting off the heating means from the time when the heating zone process is completed to the time when the soaking zone process is completed, and as an example, a furnace cooling treatment can be performed in the corresponding section, but it is not limited thereto.

[0096] [Stepwise cooling] The cold-rolled steel sheet that has been continuously annealed as described above can be cooled to form a desired structure, and it is preferable to cool the steel sheet stepwise.

[0097] In the present invention, the stepwise cooling may include primary cooling and secondary cooling. Specifically, after the continuous annealing, primary cooling may be performed at an average cooling rate of 1 to 10°C / s to a temperature range of 650 to 700°C, and then secondary cooling may be performed at an average cooling rate of 5 to 50°C / s to a temperature range of 300 to 580°C.

[0098] At this time, by carrying out the primary cooling slower than the secondary cooling, it is possible to suppress defects in the sheet shape caused by a sudden drop in temperature during the secondary cooling, which is a relatively rapid cooling period.

[0099] If the end temperature of the first cooling is less than 650°C, the carbon diffusion activity is low due to the low temperature, so the carbon concentration in the ferrite is high, while the carbon concentration in the austenite is low, resulting in an excessive hard phase fraction and an increased yield ratio. This increases the tendency for cracks to occur during processing. In addition, the cooling rate in the soaking zone and the slow cooling zone becomes excessively high, causing problems such as uneven sheet shape.

[0100] If the end temperature exceeds 700°C, an excessively high cooling rate is required during the subsequent cooling (secondary cooling). Also, if the average cooling rate during the primary cooling exceeds 10°C / s, carbon diffusion does not occur sufficiently. On the other hand, in consideration of productivity, the primary cooling process can be performed at an average cooling rate of 1°C / s or more.

[0101] As described above, after the primary cooling is completed, rapid cooling (secondary cooling) can be performed at a certain cooling rate or higher. If the end temperature of the secondary cooling is less than 300°C, the cooling variation in the width and length directions of the steel sheet may occur, resulting in deterioration of the sheet shape. On the other hand, if the temperature exceeds 580°C, the hard phase may not be sufficiently secured, resulting in a decrease in strength. In addition, if the average cooling rate during the secondary cooling is less than 5°C / s, the fraction of the hard phase may be excessive, while if it exceeds 50°C / s, the hard phase may be insufficient.

[0102] If necessary, overaging treatment can be carried out after the stepwise cooling is completed.

[0103] The overaging treatment is a process of maintaining the temperature for a certain period of time after the end temperature of the secondary cooling, and has the effect of improving the shape quality by performing a uniform heat treatment in the width direction and length direction of the coil. For this purpose, the overaging treatment can be performed for 200 to 800 seconds.

[0104] The overaging treatment can be carried out immediately after the completion of the secondary cooling, and therefore the temperature can be the same as the end temperature of the secondary cooling or within the range of the end temperature of the secondary cooling.

[0105] The high strength steel sheet according to the present invention manufactured as described above has a microstructure composed of a hard phase and a soft phase, and by maximizing ferrite recrystallization through an optimized annealing process, the steel sheet can have a structure in which hard phases, bainite and martensite, are uniformly distributed in the final recrystallized ferrite matrix.

[0106] For this reason, the steel sheet of the present invention can ensure excellent hole expandability and formability by ensuring a low yield ratio and high ductility, despite having a high strength of tensile strength of 980 MPa or more.

[0107] The present invention will be described in more detail below with reference to examples. However, the description of such examples is merely for illustrating the implementation of the present invention, and the present invention is not limited by the description of such examples. The scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom.

[0108] (Example) After preparing steel slabs having the alloy composition shown in Table 1 below, each steel slab was heated at 1200°C for 1 hour, and then finish hot-rolled at a finish rolling temperature of 880 to 920°C to produce hot-rolled steel sheets. Then, each hot-rolled steel sheet was coiled at 650°C and cooled to room temperature at a cooling rate of 0.1°C / s. Then, the coiled hot-rolled steel sheet was cold-rolled at a rolling reduction of 50% to produce cold-rolled steel sheets. Each of the above cold-rolled steel sheets was subjected to continuous annealing under the temperature conditions shown in Table 2 below, and then to stepwise cooling (primary-secondary), followed by overaging treatment at 360°C for 520 seconds to produce the final steel sheets.

[0109] In this stepwise cooling, the first cooling was performed at an average cooling rate of 3°C / s, and the second cooling was performed at an average cooling rate of 20°C / s.

[0110] The microstructure of each of the steel sheets produced as described above was observed, and the mechanical properties and plating properties were evaluated. The results are shown in Table 3 below.

[0111] In this case, the tensile test for each test piece was carried out by taking a JIS No. 5 size tensile test piece in the direction perpendicular to the rolling direction and then carrying out the tensile test at a strain rate of 0.01 / s.

[0112] On the other hand, Hole Expanding Ratio (HER) is a test to measure the ultimate deformation capacity that a steel sheet can withstand when it is subjected to a large deformation exceeding the uniform elongation rate during processing to expand and elongate a punched hole or cross section. After measuring the diameter value (df) at the time when a crack occurs during hole expansion, the HER value can be calculated (see the formula below), which was performed according to the ISO 16630 standard method.

[0113] HER = (Df-Do) / Do x 100 (%) (Do:initial punched hole diameter, Df:inner hole diameter after fracture)

[0114] The bainite phase was observed through a SEM at a magnification of 5000 after nital etching. The aspect ratio (major axis:minor axis) of the bainite grains was measured, assuming that the direction elongated from the crystal grain shape of the observed bainite phase was vertical, and the percentage of the bainite grains was measured.

[0115] The fractions of other phases were also measured using a SEM and an image analyzer after nital etching.

[0116] [Table 1]

[0117] [Table 2]

[0118] [Table 3]

[0119] As shown in Tables 1 to 3 above, in Examples 1 to 9 of the present invention, in which the alloy composition and manufacturing conditions of the steel, particularly the continuous annealing process, satisfy all of the conditions proposed in the present invention, the intended fine structure is formed, and while having high strength, the elongation rate is excellent and the hole expandability is excellent. From this, it can be confirmed that it is possible to ensure the target level of formability.

[0120] In contrast, in Comparative Examples 1 to 6, in which the continuous annealing process of the steel sheet manufacturing process was the same as in the conventional case, i.e., the end temperatures of the heating zone and the soaking zone were the same, the bainite phase was excessively elongated, and the aspect ratio (major axis:minor axis) was more than 2.3:1, failing to satisfy the physical properties targeted by the present invention. Among these, Comparative Examples 1 to 2 and Comparative Examples 4 to 5, in which the annealing temperature was relatively low, had low elongation and poor hole expandability, while Comparative Example 3 and Comparative Example 6 had yield strengths exceeding the target level.

[0121] On the other hand, in Comparative Example 7, in which the end temperature of the soaking zone was excessively high compared to the end temperature of the heating zone during continuous annealing in the steel sheet manufacturing process, the bainite phase was formed in an amount exceeding 50% by area, which was advantageous for ensuring strength, but the hole expandability was poor.

[0122] FIG. 3 shows a photograph of the microstructure of Example 4, and FIG.

[0123] In Example 4, it can be seen that a fine bainite phase and a certain fraction of martensite phase were formed in a relatively sufficient fraction of recrystallized ferrite matrix.

[0124] In contrast, in Comparative Example 6, it was confirmed that the ferrite was elongated in the rolling direction and bainite was formed in the same form. The bainite fraction increased, resulting in high yield strength and yield ratio, and poor formability.

Claims

1. A steel material comprising, by mass%, carbon (C): 0.05-0.15%, silicon (Si): 0.5% or less, manganese (Mn): 2.0-3.0%, titanium (Ti): 0.1% or less (excluding 0%), niobium (Nb): 0.1% or less (excluding 0%), chromium (Cr): 1.5% or less (excluding 0%), phosphorus (P): 0.1% or less, and sulfur (S): 0.01% or less, with the remainder consisting of Fe and unavoidable impurities; The microstructure is composed of ferrite with an area fraction of 35 to 60%, bainite with an area fraction of 40 to 50%, retained austenite with an area fraction of 3% or less, and the remainder martensite, A high-strength steel plate having excellent hole expandability, in which the average aspect ratio (long diameter:short diameter) of the bainite phase is 1.5 to 2.3:

1.

2. The high-strength steel plate having excellent hole expandability according to claim 1, wherein the martensite phase is contained in an area fraction of 15% or less (excluding 0%).

3. The high-strength steel plate having excellent hole expandability according to claim 1, wherein the steel plate has a tensile strength of 980 MPa or more, a yield strength of 680 MPa or less, and an elongation rate of 13% or more.

4. The high-strength steel plate having excellent hole expandability according to claim 1, wherein the steel plate has a yield ratio of 0.7 or less and a HER of 30% or more.

5. A method of manufacturing a steel slab comprising the steps of: heating a steel slab containing, by mass%, carbon (C): 0.05-0.15%, silicon (Si): 0.5% or less, manganese (Mn): 2.0-3.0%, titanium (Ti): 0.1% or less (excluding 0%), niobium (Nb): 0.1% or less (excluding 0%), chromium (Cr): 1.5% or less (excluding 0%), phosphorus (P): 0.1% or less, and sulfur (S): 0.01% or less, with the remainder being Fe and unavoidable impurities; a step of finish hot rolling the heated slab at an outlet temperature of Ar3 to 1000° C. to produce a hot-rolled steel sheet; coiling the hot-rolled steel sheet at a temperature in the range of 400 to 700°C; cooling the wound substrate to room temperature; After the cooling, cold rolling is performed at a rolling reduction of 40 to 70% to produce a cold-rolled steel sheet; Continuously annealing the cold rolled steel sheet; After the continuous annealing, a primary cooling step is performed to a temperature range of 650 to 700° C. and performing a second cooling step to a temperature range of 300 to 580° C. after the first cooling step. The continuous annealing step is performed in a facility equipped with a heating zone, a soaking zone, and a cooling zone, and the end temperature of the heating zone is 10 ° C. or more higher than the end temperature of the soaking zone. The manufacturing method of a high-strength steel plate having excellent hole expandability according to claim 1.

6. The manufacturing method of a high-strength steel plate having excellent hole expandability according to claim 5, wherein the end temperatures of the heating zone and the soaking zone satisfy the following relational formula. [Relationship formula] 10≦End temperature of heating zone−End temperature of soaking zone (℃)≦40

7. The manufacturing method of a high-strength steel plate having excellent hole expandability according to claim 5, wherein the end temperature of the heating zone is 790 to 830 ° C., and the end temperature of the soaking zone is 760 to 790 ° C.

8. The method for producing a high-strength steel sheet having excellent hole expandability according to claim 5, wherein the cooling after coiling is performed at an average cooling rate of 0.1 ° C. / s or less (excluding 0 ° C. / s).

9. The primary cooling is carried out at an average cooling rate of 1 to 10° C. / s, The manufacturing method of a high strength steel plate having excellent hole expandability according to claim 5, wherein the secondary cooling is performed at an average cooling rate of 5 to 50 ° C. / s.

10. The method further includes a step of overaging after the secondary cooling, The method for producing a high-strength steel plate having excellent hole expandability according to claim 5, wherein the overaging treatment is performed for 200 to 800 seconds.

Citation Information

Patent Citations

  • 1000 MPa grade alloyed hot-dip galvanized complex phase steel and preparation method thereof

    CN110129668A

  • Production of ultrahigh strength cold rolled steel sheet excellent in formability and strip shape

    JP1992289120A

  • High-strength steel having adequate workability and manufacturing method therefor

    JP2005264176A

  • High-strength cold-rolled steel sheet having excellent formability for extension flange, hot-dip galvanized steel sheet having the same formability, and method for manufacturing those

    JP2007009317A

  • High-strength steel sheet and manufacturing method therefor

    JP2009108343A